DESIGN OF QIBLAT DIRECTION USING HMc 5883L SENSOR - Sudirman Lubis; Wawan Septiawan Damanik; Munawar Alfansury Siregar (Proceeding International Seminar of Islamic Studies, 2021)
The level of accuracy of a measuring instrument is expected to be better because it is expected to provide information that can be used as a reference and benchmark in research and application in people's lives. The use of a compass measuring instrument in determining the direction of the wind and the location of the Earth's magnitude varies from year to year, such as analog and digital compasses. Both offer good readings in the same way that utilizing magnetic north and south poles as reference points. The HMC 5883L sensor is a measuring instrument that is able to detect the cardinal directions in the same way analog and digital compasses work. By using Arduino Uno as a microcontroller as a central control that is able to convert the information received from the HMC 5883L sensor into a form of data that is easy to understand. The HMC 5883L sensor is applied as a companion to the reading results of the RHI compass at the OIF Muhammadiyah University of North Sumatra to get a more accurate Qibla direction by comparing the readings of the two. The results of the HMC 5883L compass sensor readings will be visualized in the form of a pointer, a wind direction lamp and the reading will be changed in the form of a number. All data that is changed in the form of work is the result of orders from Arduino Uno received from the HMC 58883L sensor. A total of eight LED lights are used as a wind vane and are connected to the data obtained from the sensor.Keywords: HMc5883L Sensor, Qibla Direction